Nutritional advisory system using case based approach / Chew Wei Liang - Chew , Wei Liang (2003)
In today world, people are getting more and more aware of the important toward a healthy living. There is a need to cater this people with the knowledge of nutrition they want. As today, the number of nutritionists and dieticians are still not very encouraging.So to fill in the vacancies, a nutritionist advisory system should be developed to improve the current lacking. To accomplish this task, case-based reasoning seem to be a better approach. Rule-based systems need a good definition of the system and are not able to learn very well from the user choices. What is more, it is not able to handle missing information or unexpected values. on the other hand, a nutritional advisory system build wit a case-based reasoning system should be able to solve these problems. in order to show the benefits of a case-based reasoning system for a nutritional advisory system, the system will follow all the guidelines and recommendation from World Health Organization (WHO) and US RDA. The system involves a full case-based reasoning cycle and will focus very much in the adaptation part of the cycle. It will then be used to demonstrate the flexibility and adaptability of this kind of system.